2020
DOI: 10.1101/2020.03.26.20042044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the auxiliary diagnosis value of antibodies assays for the detection of novel coronavirus (SARS-Cov-2)

Abstract: Background: The spread of an novel coronavirus (SARS-CoV-2, previously named 2019-nCoV) has already taken on pandemic proportions, affecting over 100 countries in a matter of weeks. Elucidating the diagnostic value of different methods, especially the auxiliary diagnosis value of antibodies assays for SARS-CoV-2 infection is helpful for improving the sensitivities of pathogenic-diagnosis, providing timely treatment, and differentiating the infected cases from the healthy, thus preventing further epidemics. Met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The latter observation of increasing positive detection rate for IgG and/or IgM with a steady and potentially slight decrease for SARS-CoV-2 viral load has also been observed elsewhere 35,36 . SeIgG/M is higher than SeRT-PCR after the second week, which is also in line with recent evidence that the sensitivity of antibody assays overtook the RNA test on day 8 after the onset of symptoms 37 . Further, other authors also found a steep increase for antibodies, particularly in the second week, that is accompanied by a slight decrease in the probability of detection with nasopharyngeal swabs/ bronchoalveolar/sputum PCR over the first three weeks after symptom onset 38 .…”
Section: Discussionsupporting
confidence: 90%
“…The latter observation of increasing positive detection rate for IgG and/or IgM with a steady and potentially slight decrease for SARS-CoV-2 viral load has also been observed elsewhere 35,36 . SeIgG/M is higher than SeRT-PCR after the second week, which is also in line with recent evidence that the sensitivity of antibody assays overtook the RNA test on day 8 after the onset of symptoms 37 . Further, other authors also found a steep increase for antibodies, particularly in the second week, that is accompanied by a slight decrease in the probability of detection with nasopharyngeal swabs/ bronchoalveolar/sputum PCR over the first three weeks after symptom onset 38 .…”
Section: Discussionsupporting
confidence: 90%
“…In total, 4696 records based on screening of titles or abstracts and 235 after full text review were excluded. Forty studies totalling 73 study arms15161718192021222324252627282930313233343536373839404142434445464748495051525354 met the inclusion criteria. Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the studies by test method; the sum of the number of studies exceeds 40 because some evaluated more than one method. Seventy per cent (28/40) of the studies were from China,16171819202122232425262728293031323334353839404145464748 8% (3/40) from Italy,153643 and the remainder from the United States (3/40),425052 Denmark (1/40),51 Spain (1/40),37 Sweden (1/40),53 Japan (1/40),44 the United Kingdom (1/40),49 and Germany (1/40) 5433…”
Section: Resultsmentioning
confidence: 99%
“…Leukocytes (Â10⁹/L) 3.5-9.5 4.4 (3.5-5.3) 5 (25%) 4.5 (3.9-5.3) 3.7 (3.0-5.8) 0.343 Neutrophils (Â10⁹/L) 1.8-6.3 2.5 (2.2-3.2) 2 (10%) 2.5 (2.2-3.2) 2.5 (2.0-3.9) 0.970 Lymphocytes (Â10⁹/L) 1.1-3.2 1.1 (0.9-1.9) 9 (45%) 1.3 (1.0-1.9) 1.1 (0.7-1.9) 0.545 Hemoglobin ( SARS-CoV-2 provides important immunological evidence and can be an effective supplementary indicator in diagnosing the suspected cases with no detectable viral RNA (Gao et al, 2020). In our study, some patients tested negative for RT-PCR nucleic acid and IgM/IgG antibodies on admission, and the results of the viral RNA test turned positive a few days later.…”
Section: Variablesmentioning
confidence: 99%